The Development Small Medium Enterprises of Weaving Troso of Weaving Troso Asotiation in Troso Village Sub-District Pecangaan District Jepara - Chayyi, Nur; Soesilowati, Etty; Pujiati, Amin (Journal of Economic Education, 2019)
Small medium enterprises of weaving Troso are the second popular industry of Jepara, after furniture. The problems of the research are the rising raw materials, decreasing selling price, decreasing production number, reducing skilled employments. The purpose of the research is to describe profile of Tenun Troso Cluster, analyze the cost and the benefit of Tenun Troso Cluster, and create development strategy to overcome some problems faced by small medium enterprises of Tenun Troso Cluster. The research employs quantitative approach. Techniques to collect data are interview, documentation, and questionnaire. Percentage descriptive analysis, net B/C ratio, and SWOT analysis are used in the research. The result of SWOT strategy in strength aspect is the ability to respond market demand fast, and in weakness aspect is the less market information that affects the decreasing market strategy, in opportunity aspect is the products accepted by wider people, and threat aspect is more competitive competitor product. The research recommends that small medium enterprises of weaving troso in Tenun Troso Cluster is to keep cooperation among members of small medium of weaving troso in order to minimalize several problems such as raw materials, production cost, and marketing, and to increase the ability to use social